The Potential of Liquefied Oxygen Storage for Flexible Oxygen-Pressure Swing Adsorption Unit - Radek Šulc (AIDIC Servizi S.r.l., 2021)
The pressure swing adsorption (PSA) units are widely used as an oxygen source. Start-up time taking minutes is an undeniable advantage of PSA technology compared to cryogenic air separation start-up time taking hours or days. The increasing share of renewable electricity causes intraday electricity price fluctuations. These fluctuations can be an opportunity to improve the economy of a plant and/or to accumulate electricity in the form of liquefied products. This paper aims to demonstrate the possibility of a flexible PSA unit connected to a small oxy-fuel combustion unit. Two options were analyzed: i) LOX supply at electricity price peak, and ii) liquid oxygen energy storage (LOES). The cold energy needed for oxygen liquefaction will be obtained utilizing liquefied nitrogen (LIN) delivered from a large air separation unit (ASU). The analysis was carried out for the Czech Republic, the Federal Republic of Germany, and the Kingdom of Denmark. These countries differ significantly in the energy mix.